Characterizing chest pain in patients with acute coronary syndrome at Vietnam National Heart Institute: a case-control study - Lan Anh Nguyen; Nhat Minh Pham; Manh Hung Pham; Hong Nhung Nguyen Thi; Hoai Nguyen Thi; Tuan Nguyen Huu (Journal of International Medical Research)
Objective This study aimed to distinguish chest pain characteristics between patients with and without acute coronary syndrome (ACS) at Vietnam National Heart Institute. Methods A case-control study using a structured chest pain assessment questionnaire was performed to examine pain characteristics. Results Smoking, a history of heart attack, and a family history of cardiovascular disease were associated with increased ACS-related chest pain risk. Patients without ACS more frequently reported left or central chest pain, mild discomfort, pain triggered by activity, and relief with rest or nitroglycerin. ACS-related chest pain was more often characterized by pain radiating to the back, a sensation of tightness or severe discomfort, gradual intensity increase, occurrence at rest or with minimal exertion, and accompanying sweating. No significant sex differences were found in ACS-related chest pain symptoms. Conclusions Targeted assessment of chest pain features—such as pain radiation, pressure sensation, symptom escalation, duration, activity triggers, and relief factors—could improve public awareness and support the development of educational resources on ACS and non-ACS symptoms.